Remediation in rock masses - Inyang, Hilary I.; Bruell, Clifford J. (American Society of Civil Engineers, 2000)
Comprehensively presenting the complex facets of geomedia contamination modeling, site characterization, and remediation at industrial sites, landfills, and hardrock/coal mining sites, these 17 papers include theoretical analyses, case studies, recommendations, and illustrations of fundamental principles and practical techniques for characterizing rock mass pollution by such contaminants as gasoline and heavy metals, estimating contaminant flow rates, and assessing the effectiveness of innovative cleanup technologies (e.g. pneumatic and hydraulic fracturing, bioremediation).